2005
DOI: 10.3201/eid1106.040960
|View full text |Cite
|
Sign up to set email alerts
|

Nonprescribed Antimicrobial Drugs in Latino Community, South Carolina

Abstract: We investigated in a sample of Latinos the practices of antimicrobial drug importation and use of nonprescribed antimicrobial drugs. In interviews conducted with 219 adults, we assessed health beliefs and past and present behaviors consistent with acquiring antimicrobial drugs without a prescription in the United States. Many (30.6%) believed that antimicrobial drugs should be available in the United States without a prescription. Furthermore, 16.4% had transported nonprescribed antimicrobial drugs into the Un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
59
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(66 citation statements)
references
References 16 publications
3
59
0
1
Order By: Relevance
“…10,25 These include language, income, having a usual provider, and beliefs about illness and the role of medications. However, the current findings reinforce the importance of not conceptualizing minority populations according to simple and general categorizations.…”
Section: Discussionmentioning
confidence: 99%
“…10,25 These include language, income, having a usual provider, and beliefs about illness and the role of medications. However, the current findings reinforce the importance of not conceptualizing minority populations according to simple and general categorizations.…”
Section: Discussionmentioning
confidence: 99%
“…The risk factors for self-medication in this study were the age, income, and educational level. The socio-economic and educational variables are the main contributors to the self-medication practice in many countries around the world; with lower income and higher educational levels being associated with the tendency to self-medication [1,2,6,10,22]. In Jordan, the situation was different: selfmedication was associated with higher levels of income and education.…”
Section: Transparency Declarationmentioning
confidence: 99%
“…In Chile, a study (15) found that 40% of people consumed nonprescription medications during the past year. With respect to Latin American migration, in the destination country, another study (16) warned that in the USA, this community considered self-medication with antibiotics to be normal.…”
Section: Introductionmentioning
confidence: 99%